Soil Nitrate Profiles and the Risk of Nitrate Leaching in Sweet Cherry Orchards Subjected to Different Management Schemes - San Martino, Liliana (2014)
When nitrogen is applied to sweet cherry orchards, losses can take place. The authors determined the soil nitrate distribution in fertilized sweet cherry orchards in Southern Patagonia (Argentina). The treatments were irrigation (drip vs. furrow), soil cover (bare soil vs. grass sward), and fertilization (N vs. NPK). Soil samples were taken in the row and the alley to a depth of 120 cm and nitrates were determined. Soil cover was significant and the irrigation system and fertilization were less important. The grass sward in the alleys is an important factor for sustainable sweet cherry orchard management, because it reduces the risk of nitrate leaching.